Causal Effects of Inflammatory Cytokines and Immune Cell Phenotypes on Spontaneous Abortion: Evidence From Mendelian Randomization - Lin S; Tian X; Kong S; Zhang B; Wang S; Zhu K; Liu X; Yeung WSB; Cao D; Yao Y (International Journal of Women's Health)
Shaochong Lin,1– 3,* Xiangming Tian,4,* Sijia Kong,5 Bolun Zhang,1– 3 Sidong Wang,2,6 Kongfu Zhu,2 Xiaomin Liu,7,8 William S B Yeung,2,6 Dandan Cao,2 Yuanqing Yao1– 3 1School of Medicine, Nankai University, Tianjin, People’s Republic of China; 2Shenzhen Key Laboratory of Fertility Regulation, Reproductive Medicine Center, The University of Hong Kong-Shenzhen Hospital, Shenzhen, People’s Republic of China; 3Department of Obstetrics and Gynecology, The First Medical Center of Chinese PLA General Hospital, Beijing, People’s Republic of China; 4Medical Center for Human Reproduction, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 5Department of Obstetrics and Gynecology, Peking University Shenzhen Hospital, Shenzhen, People’s Republic of China; 6Department of Obstetrics and Gynecology, LKS Faculty of Medicine, The University of Hong Kong, Hong Kong Special Administrative Region, People’s Republic of China; 7Shenzhen Key Laboratory of Human Commensal Microorganisms and Health Research, Shenzhen, People’s Republic of China; 8College of Life Sciences, University of Chinese Academy of Sciences, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuanqing Yao, Shenzhen Key Laboratory of Fertility Regulation, Reproductive Medicine Center, The University of Hong Kong-Shenzhen Hospital, No. 1 haiyuan 1st Road, Futian District, Shenzhen, People’s Republic of China, Email yaoyq_hkuszh@126.com Dandan Cao, Shenzhen Key Laboratory of Fertility Regulation, Reproductive Medicine Center, The University of Hong Kong-Shenzhen Hospital, No. 1 haiyuan 1st Road, Futian District, Shenzhen, People’s Republic of China, Email caodd@hku-szh.orgPurpose: This study aims to investigate the causal relationship between inflammatory cytokines, immune cells and spontaneous abortion (SA).Methods: A bidirectional two-sample Mendelian randomization (MR) analyses was conducted based on the genetic data of 91 inflammatory cytokines (n=14,824), 731 immune traits (n=3757) and SA (18,680 cases and 162,987 controls) cohorts. Five different MR analysis methods and Bayesian-weighted Mendelian randomization (BWMR) analysis were employed to assess the genetic causal connection. In addition, the robustness of this study results was ensured through comprehensive sensitivity analyses assessing heterogeneity, and potential horizontal pleiotropy and reverse causality.Results: These MR results suggest that higher levels of two inflammatory cytokines and ten immune cells are associated with a lower risk of SA (OR < 1.00). In contrast, fifteen immune cell traits exhibit a positive relationship with SA risk (OR > 1.00). Notably, mediation analysis revealed that the causal effect of programmed death ligand 1 (PDL1) on SA was partially mediated by CD45 expression on Granulocytic Myeloid-Derived Suppressor Cells (GR-MDSCs), and Terminally Differentiated CD4⁻CD8⁻ T cells also acted as mediators in the causal effect of tumor necrosis factor-beta (TNF-β) on SA.Conclusion: This study comprehensively assessed the causal relationship between immune-related exposures and SA, identifying several immune factors associated with SA risk. These finding have implications for clinical guidance in pregnancy preparation.Keywords: inflammatory cytokine, immune cell, Mendelian randomization, spontaneous abortion